EXPERIMENTAL STUDY OF CRACK LENGTH MEASUREMENTS USING ELECTRICAL POTENTIAL DROP METHOD (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
The paper present some main experimental results on fatigue crack detection using Electrical Potential Drop technique (EPD) under constant stress amplitude. The potential drop electrical circuit was designed and manufactured as well as tested using the flat fatigue specimens of aluminum alloy 7075-T6. The experimental analysis showed that the electrical potential drop circuit capable for detecting the fatigue crack during the test and it gave satisfactory crack length results observation compared to the actual lengths for fatigue long cracks